2017
DOI: 10.1016/j.cgh.2016.12.036
|View full text |Cite
|
Sign up to set email alerts
|

High Dietary Intake of Specific Fatty Acids Increases Risk of Flares in Patients With Ulcerative Colitis in Remission During Treatment With Aminosalicylates

Abstract: Background & Aims Dietary factors may have a significant role in relapse of disease among patients with ulcerative colitis (UC). However, the relationship between diet and UC is inadequately understood. We analyzed data from the diet’s role in exacerbations of mesalamine maintenance study to determine whether dietary factors affect risk of disease flares in patients with UC. Methods We performed a prospective, multi-center, observational study of 412 patients, from 25 sites, with UC in remission during monot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 34 publications
0
38
0
3
Order By: Relevance
“…In addition to excess adipose tissue, diet quality also plays a role in the regulation of the intestinal microbiome and can further augment the associated inflammatory conditions [ 7 10 ]. Diet quality deserves increased attention not only for modulating inflammation, but also to avoid nutritional deficiencies and manage symptoms in those with IBD [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to excess adipose tissue, diet quality also plays a role in the regulation of the intestinal microbiome and can further augment the associated inflammatory conditions [ 7 10 ]. Diet quality deserves increased attention not only for modulating inflammation, but also to avoid nutritional deficiencies and manage symptoms in those with IBD [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Die Autoren folgerten daraus, dass bestimmte Fette bei Wirten mit entsprechender genetischer Veranlagung möglicherweise IBD begünstigen können [109]. Eine kürzlich publizierte Prospektivstudie mit CU-Patienten ergab ein dreimal höheres Risiko für ein Wiederaufflammen der Krankheit bei Patienten, die bestimmte Fettsäuren wie Myristinsäure (enthalten in Palm- und Kokosnussöl sowie in Milchfett) konsumierten, sowie bei Patienten, die ALA zu sich nahmen [110]. Dieses Ergebnis mag überraschend erscheinen, da ALA zur Gruppe der n-3-PUFA zählt, denen eine entzündungshemmende Wirkung zugeschrieben wird [48].…”
Section: Ernährung Und Krankheitsverlaufunclassified
“…In addition, supplementation with omega-3 free fatty acids was reported as not effective for the prevention of relapse in CD (Feagan et al, 2008;Lev-Tzion, Griffiths, Leder, & Turner, 2014). More recently, a prospective, multicenter study of patients with UC in remission on aminosalicylate therapy revealed that increasing intake of myristic acid (commonly found in palm oil, coconut oil, and dairy fats) was associated with disease relapse (Barnes, Nestor, Onyewadume, de Silva, & Korzenik, 2017). Other foods, such as processed meat, alcohol, and foods high in sulfur, were not associated with an increased risk of flare (Barnes et al, 2017).…”
Section: The Role Of Food and Dietmentioning
confidence: 99%